Fully Supramolecular Polyrotaxanes as Biphase Drug Delivery Systems. (2nd December 2014) - Massoudi, Abdolhossien; Adeli, Mohsen; Khosravi far, Leila
Abstract : Pseudopolyrotaxanes (PPR) consisting of α -cyclodextrin rings and polyethylene glycol axes with end thymine groups have been synthesized and characterized successfully. Fluorescein (Fl) as a model drug was conjugated to the hydroxyl functional groups of cyclodextrin rings of PPR via ester bonds and PPR-Fl as the primary drug delivery system was obtained. Finally PPR-Fl was capped by hydrogen bonds between end thymine groups and a suitable complementary molecule such as polycitric acid, citric acid, or adenine. The aim of this work was to control the release of the fluorescein-cyclodextrin (Fl-CD) conjugates, as the secondary drug delivery systems, from PPR-Fl by controlling the noncovalent interactions between stoppers and thymine end groups. It was found that the rate of release of the Fl-CD from PPR-Fl could be controlled by pH and the ratio of citric acid or adenine to the PPR-Fl.